2006
DOI: 10.1159/000095647
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Intake from Food and Liquid in Japanese Children Living in Two Areas with Different Fluoride Concentrations in the Water Supply

Abstract: The purpose of this study was to estimate the average daily amount of fluoride from the diet ingested by Japanese children of ages susceptible to dental fluorosis in two areas with different fluoride concentrations in the water supply. Thirty-eight children aged 2–8 years participated in a survey of fluoride intake. Twenty-one out of 38 children lived in an area in which the community water fluoride concentration was an average of 0.555 ppm (moderate fluoride area: MFA), and 17 lived in a low fluoride area (LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The resultant powdered milk sample was reconstituted as a derived sample of 20 ml milk with one of several water F concentrations; distilled water, and 0.2, 0.6, 0.8 and 1.4 g F/ml drinking water according to those meeting the Japanese water regulations and the findings in previous reports [Tsutsui et al, 2000;Nohno et al, 2006]. The F concentration of each of the 5 derived milk samples was then measured in triplicate using an F ion selective electrode and the HMDS diffusion method as previously described.…”
Section: Analysis Of F Concentrationmentioning
confidence: 99%
“…The resultant powdered milk sample was reconstituted as a derived sample of 20 ml milk with one of several water F concentrations; distilled water, and 0.2, 0.6, 0.8 and 1.4 g F/ml drinking water according to those meeting the Japanese water regulations and the findings in previous reports [Tsutsui et al, 2000;Nohno et al, 2006]. The F concentration of each of the 5 derived milk samples was then measured in triplicate using an F ion selective electrode and the HMDS diffusion method as previously described.…”
Section: Analysis Of F Concentrationmentioning
confidence: 99%
“…We should pay attention to the Japanese culture when we look at the total fluoride intakes due to Japanese traditional green tea drinking or, in other words, changing barley tea to green tea. Nohno et al [2006] reported that the caries-preventive effect was confirmed in the moderate-fluoride area, where the average total fluoride intake from the diet was 0.0252 mg/kg/day in 2-to 5-year-old children. So in the Pacific climate zone with an annual temperature of 16 ° C, a glass of green tea (0.7 mg/l) in place of barley tea for children could bring the fluoride intake value closer to the level which, while not sufficient, is effective in caries prevention to some extent.…”
Section: Discussionmentioning
confidence: 94%
“…This is probably because the number of foods used in the market basket technique is still limited, as almost all the fluoride data in the method are mainly based on uncooked foods and the fluoride concentration of tap water for cooking is not taken into account except for boiled rice. Nohno et al [2006] found that the fluoride intake from boiled rice reflected the fluoride concentration of cooking water. Song et al [2004] reported that when water was boiling, the total amount of fluoride in the water decreased as time passed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations